ANALISIS DISTRIBUSI BEBAN VELG SEPEDA MOTOR LISTRIK DENGAN VARIASI MOTIF SPOKE MENGGUNAKAN METODE ELEMEN HINGGA - Kurnia Illahi, Putra; Karohika, I Made Gatot; Parwata, I Made (Teknik Desain Mekanika, 2023)
Abstract Motorcycles are something that everyone needs. The types of motorbikes are also increasingly varied, one of which is an electric motorbike. An important component of an electric motorcycle is the wheels. Wheels have an important role as attachment to the tire and also distribute the power generated by the engine. Wheels are designed to have high strength to withstand a given load. With the development of computer technology, it allows us to do simulations or tests of the strength and safety values of wheels to avoid wheel failure. This study aims to determine the strength and safety value of the wheels with variations in the spoke model through the simulations carried out. The simulation was carried out using the Autodesk Inventor 2021 software. The load given was in the form of a static load (force) of 800 N and a dynamic load (moment) of 4000 N.mm. From the simulations carried out, it was found that type A wheels have a von misses stress of 66.29 MPa, a displacement of 0.09254, and a safety factor of 4.15. Wheels with type B have a von misses stress of 37.02 MPa, a displacement of 0.08067, and a safety factor of 7.43. While vekg with type C has a von misses stress of 38.71 MPa, a displacement of 0.07182, and a safety factor of 7.1. Keywords: Wheels, Simulation, Safety factor